Updating Adoption - Ralph L. Hamilton (Journal of Applied Communications, 1973)
THE TASK OF UPDATING adoption is an overwhelming one. First, there is a wealth of information on the subject. Second, there is most likely an extremely wide range of knowledge on this subject among members of this audience.